DAKWAH AKHLAK MELALUI LITERASI (Kajian terhadap Kitab Syiiran Nasehat Karya K.H. R. Asnawi) - nur khosiin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2015)
The way KH. R. Asnawi spread the Islamic religion, especially in terms of moral building is conducted through various ways, including madrassas, boarding school, mosque committees and compiling book of advices which is said to be literary works in the form of poems containing moral education, moral teaching among human being and in relation with God and His Massenger. The research is using interviews and documentation and descriptive-interpretative approach. The primary data source is the poem book and the secondary source is advice relating to works. While the data analysis technique is using psycho-historical hermeneutic and descriptive method. The resultshows that there is a value of moral education in the book of poem advice. The book is about the moral education towards Allah, the Prophet and human beings all of which is considered as the basis and foundation by KH. R Asnawi in the preaching and building the morals of the people.